Venous identity requires BMP signalling through ALK3 - Neal, Alice; Nornes, Svanhild; Payne, Sophie; Wallace, Marsha D.; Fritzsche, Martin; Louphrasitthiphol, Pakavarin; Wilkinson, Robert N.; Chouliaras, Kira M.; Liu, Ke; Plant, Karen; Sholapurkar, Radhika; Ratnayaka, Indrika; et al. (Nature communications, 2019)
Venous endothelial cells are molecularly and functionally distinct from their arterial counterparts. Although veins are often considered the default endothelial state, genetic manipulations can modulate both acquisition and loss of venous fate, suggesting that venous identity is the result of active transcriptional regulation. However, little is known about this process. Here we show that BMP signalling controls venous identity via the ALK3/BMPR1A receptor and SMAD1/SMAD5. Perturbations to TGF-β and BMP signalling in mice and zebrafish result in aberrant vein formation and loss of expression of the venous-specific gene Ephb4 , with no effect on arterial identity. Analysis of a venous endothelium-specific enhancer for Ephb4 shows enriched binding of SMAD1/5 and a requirement for SMAD binding motifs. Further, our results demonstrate that BMP/SMAD-mediated Ephb4 expression requires the venous-enriched BMP type I receptor ALK3/BMPR1A. Together, our analysis demonstrates a requirement for BMP signalling in the establishment of Ephb4 expression and the venous vasculature. The establishment of functional vasculatures requires the specification of newly formed vessels into veins and arteries. Here, Neal et al. use a combination of genetic approaches in mice and zebrafish to show that BMP signalling, via ALK3 and SMAD1/5, is required for venous specification during blood vessel development.